Functional changes in standardized single-family houses: legal and political issues / Tipinio gyvenamojo namo architektūros funkcinė kaita: teisinės ir politinės prielaidos - Aistė Galaunytė (Mokslas: Lietuvos Ateitis, 2017)
During the years of soviet occupation, housing policy was one of the most important state issues and projects of standardized designs were authorized and distributed by the state. Legal architecture parameters and regulations of soviet times, although their actual validity expired, are visible in todays modern, especially non-elite, standardized architecture. One can identify “traditions” formed by soviet law in contemporary single-family houses or even in legal regulations. The study examines and compares soviet and contemporary legal regulations and their impact on typical single-family houses architecture. The study is contextualized by invoking historical and social evaluations of the period.